2009
DOI: 10.4103/1463-1741.45310
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic ototoxicity due to noise exposure and aminoglycoside antibiotics

Abstract: Acoustic exposure to high intensity and/or prolonged noise causes temporary or permanent threshold shifts in auditory perception, reflected by reversible or irreversible damage in the cochlea. Aminoglycoside antibiotics, used for treating or preventing life-threatening bacterial infections, also induce cytotoxicity in the cochlea. Combined noise and aminoglycoside exposure, particularly in neonatal intensive care units, can lead to auditory threshold shifts greater than simple summation of the two insults. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 77 publications
2
33
0
Order By: Relevance
“…Scattered evidence, moreover, supports the expectation that sub-injurious noise and sub-clinical ototoxic exposure will interact synergistically to produce hearing loss in young humans and animals (Bernard, 1981; Henley and Rybak, 1995; Li and Steyger, 2009). However, in a recent attempt to document this type of synergy in young CBA/J mice (Fernandez et al, 2010), we unexpectedly observed dramatic protection against permanent noise-induced hearing loss (NIHL) by sub-chronic application of low-dose kanamycin (KM, 300 mg/kg sc, 2x/day, postnatal day 20–30).…”
Section: Introductionmentioning
confidence: 84%
“…Scattered evidence, moreover, supports the expectation that sub-injurious noise and sub-clinical ototoxic exposure will interact synergistically to produce hearing loss in young humans and animals (Bernard, 1981; Henley and Rybak, 1995; Li and Steyger, 2009). However, in a recent attempt to document this type of synergy in young CBA/J mice (Fernandez et al, 2010), we unexpectedly observed dramatic protection against permanent noise-induced hearing loss (NIHL) by sub-chronic application of low-dose kanamycin (KM, 300 mg/kg sc, 2x/day, postnatal day 20–30).…”
Section: Introductionmentioning
confidence: 84%
“…These include the organic solvents (Chen & Henderson, 2009; Hoet & Lison, 2008), cisplatin (Gratton et al, 1990), antibiotic aminoglycosides (Li & Steyger, 2009), and opiates (Rawool & Dluhy, 2011). One difference between MDMA and the above toxic agents is that the latter have some ototoxicity when used alone, whereas MDMA alone caused no ototoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Heightened ototoxic injury may be more closely tied to metabolic characteristics of the immature cochlea (e.g., Zelck et al, 1993; Whitlon et al, 1999), while the underpinnings of the longer sensitive period for noise remain unclear. Although it is difficult to superimpose findings in altricial mammals (such as rodents) onto precocial mammals as are humans, studies suggest that neonates and children are particularly vulnerable to both noise and ototoxins (Bernard, 1981; Henry et al, 1981; Henley and Rybak, 1995; Kent et al, 2002; Li and Steyger, 2009). Moreover, recent years have seen increasing interest in potential delayed and long term effects of prenatal and early postnatal environments in both animals and humans (Kujawa and Liberman, 2006; Ohlemiller, 2008; Kujawa and Liberman, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, loci have been identified that modulate cochlear injury associated with aging (Willott, 1991; Erway et al, 1993; Van Eyken et al, 2007; Ohlemiller and Frisina, 2008; Rodriguez-Paris et al, 2008), noise (Erway and Willott, 1996; Ohlemiller, 2006, 2008; Konings et al, 2009; Pawelczyk et al, 2009), and ototoxins (Forge and Schacht, 2000; Rybak, 2007; Perletti et al, 2008) in humans and animals. Susceptibility to noise and ototoxins is not constant throughout life, but depends on age, such that young humans and animals appear especially vulnerable (Stanek et al, 1977; Bernard, 1981; Henry, 1982b; Saunders and Chen, 1982; Henry, 1983; Henley and Rybak, 1995; Li and Steyger, 2009). The physiologic basis of this ‘sensitive period’ (alternately termed ‘critical period’ or ‘early window’), is not well understood, but probably differs for noise versus ototoxins.…”
Section: Introductionmentioning
confidence: 99%